Network orchestration for knowledge mobility: The case of an international innovation community - Pia Hurmelinna-Laukkanen; Satu Nätti (jbm - Journal of Business Market Management, 2012)
This study aims to increase understanding on how relatively vague aggregations of firms can be directed in a manner that facilitates innovation. In particular, we examine promotion of knowledge mobility as a part of innovation network orchestration. Literature review and a case study of an international innovation community indicate, first, that of prerequisites to knowledge mobility, common language and codification of knowledge are relevant, and, second, that regarding the orchestration activities, maintaining a balance between autonomous flexibility and network direction together with neutrality are needed in order to build common identity and trust required for knowledge mobility.
urn:nbn:de:0114-jbm-v5i4.321
Keywords: 650; knowledge mobility; international; innovation; network; community; case-study